Due letture dell’esordio della lettera 64 di Seneca. 1. La simbologia del fumo - Gazzarri, Tommaso (Lucius Annaeus Seneca, 2021)
This article offers an analysis of Ep. 64 and, in particular, of the thematic role played by the initial image of the fumus modicus. Although the text of the Epistle presents a rather fluid transition through a series of images and considerations, much in the vein of Senecan philosophical sermo, the element of the smoke crucially contributes to the internal coherence of the text. On the one hand, Seneca bends for his philosophical purposes Horace’s mention of the fumus in the Ars Poetica, which illustrates a specific literary ideal there. On the other hand, Seneca leverages the shared physical qualities of both fumus and animus to create the thematic unity of the Epistle, which repeatedly insists on the nature of a healthy and sound mind.